Gut health benefits of brown seaweed Ecklonia radiata and its polysaccharides demonstrated in vivo in a rat model. (October 2017) - Charoensiddhi, Suvimol; Conlon, Michael A.; Methacanon, Pawadee; Franco, Christopher M.M.; Su, Peng; Zhang, Wei
Highlights: Ecklonia radiata and its polysaccharides improve gut health in vivo differently. Whole seaweed reduces toxic protein fermentation products and pathogenic bacteria. Seaweed polysaccharides increase stool bulk, SCFA, and key butyrate-producer. Seaweed polysaccharides consist mainly of fucoidan and alginate. The brown seaweed Ecklonia radiata has potential as a source of prebiotics. Abstract: We examined the gut health potential of the brown seaweed Ecklonia radiata and its polysaccharides. Rats consumed an AIN-93G-based diet without addition (control) or containing 5% (w/w) of ground dried whole seaweed (WS) or dried powdered polysaccharide fraction (PF) of the seaweed for 1 wk. The PF consisted largely of fucoidan and alginate. PF treatment increased cecal digesta weight relative to the control (1.36 ± 0.17 vs 0.60 ± 0.06 g/100 g body weight). Beneficial cecal total short chain fatty acids increased in response to WS (213.25 ± 14.40 μmol) and PF (208.59 ± 23.32 μmol) compared with the control (159.96 ± 13.10 μmol). Toxic protein fermentation product levels were decreased by WS and PF. Cecal numbers of bacteria relevant to gut health were determined using quantitative real-time PCR. Relative to the control, numbers of butyrate-producing Faecalibacterium prausnitzii were increased by PF supplementation, whereas WS decreased numbers of potentially pathogenic Enterococcus . In conclusion, E. radiata -derived polysaccharides have promise as prebiotic supplements.